Geography and archeology: spatial and contextual analysis of archaeological sites in the Amazonian estuary - Senna, Cristina do Socorro Fernandes (GEOUSP Espaço e Tempo (Online), 2016)
The archaeological research on Amazon Basin during the last fifty years utilized conventional approach to investigate archaeological sites for heritage conservation due the strong impact caused by mineral exploration projects. Therefore, new approaches utilizing Landscape Ecology approach shows the integration among different scientific disciplines as archaeology, geophysics, botany, soil science, and geography for integrated analysis of the human occupation of the Amazon estuary during the last millennium. The results show 3 archaeological sites related to Tupi-Guarani Cultural Tradition, dated 14C method between 980±40 BP. and 110±40 BP.